Analysis of cutting forces during grinding of titanium alloy and corrosion-resistant steel by diamond, electrocorundum and cubic borine nitrid wheels - Lebedev, Vladimir; Chumachenko, Tatiana; Bespalova, Alla; Nikolaeva, Tatiana; Omelchenko, Yevhen (Technology audit and production reserves, 2021)
The object of research is the process of circular and surface grinding of titanium alloy and corrosion-resistant steel, namely, the cutting forces arising from mechanical processing. One of the most problematic areas in work is the selection of the required grinding modes, material and grinding wheel grain size. In the course of the experiment, we used samples of VT8 titanium alloy and 12Х18N9T steel, on which the grinding process was studied with wheels made of various materials (electrocorundum, cubic boron nitride (CBN), diamond). The values of the cutting forces Py and Pz were obtained in the latitude of permissible modes, which are most often used in circular and flat grinding, and can reach maximum values, respectively, Py=27 N, Pz=15.5 N. The data were obtained at a low wheel speed from electrocorundum, about 15 m/s and grain size 8. By reducing the grain size of the wheel, we get the effect of increasing the energy consumption of the grinding process, due to the increase in the values of the cutting forces. If we compare the cutting forces arising from grinding with different wheels, then the following can be noted. Compared to electrocorundum wheels, when using CBN wheels, the cutting forces are reduced by 20–25 %, and when grinding with diamond wheels (despite the high wear of the diamond wheel), the effect of cutting forces is reduced by 25–30 %. This is due to the fact that cutting conditions are the most favorable for diamond and CBN grains, which makes it possible to use more intense cutting conditions. The results of the study allow predicting the performance of the grinding wheel, reducing the energy consumption of production, and also adjusting the processing mode of the part to obtain the necessary quality indicators of the surface layer and the geometric dimensions of the part.